The capital markets : evolution of the financial ecosystem - Strumeyer, Gary; Swammy, Sarah (Hoboken : Wiley, 2017)
"The Capital Markets: evolution of the financial ecosystem is the new standard providing practical text book style coverage of this dynamic market and its products. Written by the former President of BNY Mellon Capital Markets, LLC for both financial professionals and novices, The Capital Markets provides a comprehensive macro view of the marketplace and how its products operate. This book is the definitive resource and the companion text to The Capital Markets website. The subject matter offers an authoritative discussion of the fundamentals of both, the fixed income and equity markets, underwriting, securitizations, derivatives, currency among other products through the lens of leading industry practitioners. Key Learning Concepts Understand the impact of both global and domestic regulatory changes Learn about the products that holistically make up the capital markets Explore the components of the infrastructure that underpins these markets Examine the tools used for trading and managing risk Review new product innovations"--
Machine generated contents note: Preface xi Acknowledgments xiii About the Author & Executive Editor xv About the Contributors xvii PART ONE Introduction and Tools CHAPTER 1 The Early 21st-Century Evolution of Global Capital Markets 3 Jack Malvey CHAPTER 2 The Role of Global Capital Markets 20 Christian A. Edelmann and Shasheen Jayaweera CHAPTER 3 How the Global Financial Crisis Transformed the Industry 52 Christian A. Edelmann and Pete Clarke CHAPTER 4 Cash Bonds and Futures 64 Amir Sadr CHAPTER 5 Risk in Capital Markets 89 Peter Reynolds and Mike Hepinstall CHAPTER 6 Enablers for Robust Risk Management in Capital Markets 110 Swati Sawjiany CHAPTER 7 Making Markets Work 120 Eric Czervionke PART TWO Capital Markets Products CHAPTER 8 Money Markets 157 Randy Harrison and Paul Mandel CHAPTER 9 Repurchase Agreements 184 Karl Schultz and Jeffrey Bockian CHAPTER 10 U.S. Treasury and Government Agency Securities 205 Lee Griffin and David Isaac CHAPTER 11 Government-Sponsored Enterprises and Federal Agencies 210 David Isaac and Francis C. Reed, Jr. CHAPTER 12 Inflation-Linked Bonds 232 Henry Willmore CHAPTER 13 Mortgage-Backed Securities 239 Patrick Byrne CHAPTER 14 Corporate Bonds 254 Marvin Loh CHAPTER 15 Preferred Stock 286 Sarah Swammy CHAPTER 16 Distressed Debt Securities 296 Michael McMaster CHAPTER 17 Securitization 304 Daniel I. Castro, Jr. CHAPTER 18 Asset-Backed Securities 312 Daniel I. Castro, Jr. CHAPTER 19 Non-Agency Residential Mortgage-Backed Securities (RMBSs) 329 Daniel I. Castro, Jr. CHAPTER 20 Commercial Mortgage-Backed Securities (CMBSs) 348 Daniel I. Castro, Jr. CHAPTER 21 Collateralized Debt Obligations (CDOs) 361 Daniel I. Castro, Jr. CHAPTER 22 Structured Investment Vehicles (SIVs) 381 Daniel I. Castro, Jr. CHAPTER 23 Collateralized Loan Obligations (CLOs) 389 Mendel Starkman CHAPTER 24 Municipal Bonds 419 Fred Yosca CHAPTER 25 Equities 435 David Weisberger CHAPTER 26 Cash Equities in the Secondary Market 458 Eric Blackman and Robert Grohskopf CHAPTER 27 Exchange-Traded Funds (ETFs) 469 Reginald M. Browne CHAPTER 28 Equity Capital Markets 481 Daniel C. de Menocal, Jr. CHAPTER 29 Interest Rate Swaps 503 Amir Sadr CHAPTER 30 Interest Rate Options 523 Amir Sadr CHAPTER 31 Commodities 548 Bob Swarup CHAPTER 32 Currency 571 Simon Derrick CHAPTER 33 Conclusion 578 Gary Strumeyer and Christian Edelmann Index 591.
Includes index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Capital market; Finance; Electronic books